Fatal Bacillus cereus bacteremia in a patient with diabetes. - Orrett, F. A. (National Medical Association, 2000)
This report describes a fatal case of Bacillus cereus septicemia in a patient with uncontrolled diabetes and re-emphasizes the potential seriousness of Bacillus infections in patients with compromised immune function.